2015
DOI: 10.1007/s00606-015-1195-0
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of Rosa soulieana (Rosaceae) in the Hengduan Mountains: refugia and ‘melting’ pots in the Quaternary climate oscillations

Abstract: The Hengduan Mountains is the core of the Sino-Himalayan Floristic Region. Different views have been postulated from phylogeographic studies in understanding the historical biological events shaping presentday distributions and species diversities in this area. We analyzed the phylogeography of Rosa soulieana, a widely distributed rose species in dry and semi-dry valleys of the Hengduan Mountains of southwestern China using two cpDNA intergenic spacers. 9 cpDNA haplotypes were confirmed in 650 individuals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…According to the genetic structure of R . soulieana based on AFLP genotypes in this study and the cpDNA haplotypes reported by Jian et al [ 16 ], it is preferable to collect and preserve the populations in southeastern Tibet, northwestern Yunnan and along the Yalongjiang River during wild rose germplasm collection. Furthermore, when choosing this wild rose as a plant for the ecosystem restoration of the dry and hot valleys in the Hengduan Mountains, it is better to choose propagation materials from the east of the Yalongjiang River for the revegetation of areas in the Mountain Warm Zones, and to choose propagation materials from the west of Yalongjiang River for the revegetation of areas in the Qinghai-Xizang Plateau Cold Climate Realm.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…According to the genetic structure of R . soulieana based on AFLP genotypes in this study and the cpDNA haplotypes reported by Jian et al [ 16 ], it is preferable to collect and preserve the populations in southeastern Tibet, northwestern Yunnan and along the Yalongjiang River during wild rose germplasm collection. Furthermore, when choosing this wild rose as a plant for the ecosystem restoration of the dry and hot valleys in the Hengduan Mountains, it is better to choose propagation materials from the east of the Yalongjiang River for the revegetation of areas in the Mountain Warm Zones, and to choose propagation materials from the west of Yalongjiang River for the revegetation of areas in the Qinghai-Xizang Plateau Cold Climate Realm.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, morphological characteristics are not always able to detect taxonomic diversity [ 54 ]. Although 4 intraspecific varieties have been distinguished according to variable morphological characteristics, this intraspecific classification was not confirmed by detected cpDNA haplotype variation [ 16 ]. Based on the Bayesian analysis and NJ clustering, the genotypes of R .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the last decade, a number of phylogeographic studies have investigated the link between organismic evolution of plant species and the geologic uplift associated with climate changes in the HHM and QTP (Qiu et al, 2011;Jian et al, 2015;Luo et al, 2016). For instance, phylogeographic studies on Primula tibetica related to the effects of Quaternary climatic oscillations in QTP (Ren et al, 2017a), Metrocoris sichuanensis concerned with geological effects in Sichuan Basin (Ye et al, 2018), and Allium section Sikkimensia linked with Hengduan Mountains massif uplift (Xie et al, 2019).…”
Section: Introductionmentioning
confidence: 99%